Academic Achievement in Young Adults with a History of Adolescent Physical Abuse - Pelcovitz, David; Pelcovitz, Michelle; Sunday, Suzanne; Labrunad, Victor; Lehrman, Decla; Kline, Myriam; Salzingerg, Suzanne; Kaplan, Sandra (Adolescent Psychiatry, 2017)
Background/Objective: About 16% of documented cases of maltreatment take place in adolescence, a developmental period which carries unique vulnerability. Studies investigating the impact of physical abuse find negative outcomes in cognitive functioning and academic performance, both in the short and long term. The present study aims to examine the impact of documented adolescent physical abuse on adolescent and adult academic functioning. Methods: This longitudinal study is comprised of two waves of data following a cohort of individuals who were physically abused in adolescence and a non-abused comparison group. We assessed academic and occupational achievement of 145 young adults (67 abused, 78 non-abused) via academic records, standardized achievement test scores, parental academic achievement, IQ, and teacher ratings of internalizing and externalizing behaviors at time 1 and the highest academic degree, current work status, history of job loss at time 2 (10-14 years later). Results: School performance of the abused participants at time 1 showed lower grades and achievement scores, more teacher-rated problems, and more special school services than the comparison group. At the second time, the abused group completed significantly fewer years of schooling and was more likely to have lost a job. Grades at the first time, gender, parents' education, and an abuse status by IQ interaction were significant predictors of the number of years of schooling at the second time. Conclusion: This study highlights the pervasive impact that adolescent physical abuse can have on academic functioning and documents how these difficulties can set the stage for continuing challenges in young adulthood.
Keywords: physical abuse